THE INFLUENCE OF COMIC STRIPS TOWARDS STUDENTS’ READING COMPREHENSION ON RECOUNT TEXT - NABILA SHAFIRA; EVA NURCHURIFIANI; FEBRIYANTI (English Department, STKIP PGRI Bandar Lampung, 2022)
This research aimed to know the influence of comic strips towards students’ reading comprehension. This technique helped the students to comprehend the story by imagining it with the strip of pictures. The objective of the research was to know the influence of comic strips towards students’ reading comprehension in recount text. In this research the writer used experimental method or known as descriptive quantitative research. The population was 48 students in 2 classes. The sample was taken by using Total Sampling Technique. The writer took all of the classes as the sample of research namely experimental and control class. It consisted of 45 students; the other students were absence. The main technique in measuring students’ reading comprehension was multiple choice which consisted of 40 items test. Each item has four options a,b,c, and d. The score each item was 2.5. In calculating the data analysis, the writer used t-test formula. Based on the data analysis, the writer got the result that was accepted. It was obtained that = 4.45, for α= 0.05 was 1.68 and for α=0.01 was 2.42 (4.45 > 1.68 < 2.42). So, was accepted. It meant that there was significant influence of comic strip toward students’ reading comprehension on recount text at the tenth grade of SMA Negeri 8 Bandar Lampung in 2021/2022. Based on the result of the research, it is clear that comic strips had an influence to the students’ reading comprehension, especially in recount text.